Complex Temporalities and Shared Reading: Picturebooks in the Anthropocene - Vanhove, Jonas (Cahier voor Literatuurwetenschap, 2024)
Starting from the notion that the current environmental crisis challenges traditional notions of temporality, this article argues that children’s picturebooks are uniquely positioned to help engender a ‘critical temporal literacy’ (Huebener 2020, 24). The combination of different modes (visual, tactile and textual) in picturebooks can offer innovative representations of alternative temporalities. Furthermore, as picturebooks are usually the first books encountered by new readers, the reading practice is often shared between generations which raises opportunities for intergenerational thinking and communication. I discuss three contemporary picturebooks (Once Upon A Time There Was And Will Be So Much More by Johanna Schaible; Tales From The Inner Cities by Shaun Tan; Seasons by Blexbolex) that employ different literary strategies to enrich human temporalities through contact with the nonhuman.